THEORETICAL ASPECTS REGARDING THE NEW OFFENSE COVERED BY ART. 246 OF THE CRIMINAL CODE MISSAPPROPRIATION OF PUBLIC AUCTIONS AND OFFENCES COVERED BY ART. 65 OF LAW NO. 21/1996 REPUBLISHED. COMPETITION LAW - Rodica Aida POPA (Challenges of the Knowledge Society)
The present study aims to bring to the attention of the legal law specialists the theoretical aspects related to a new incrimination as the one covered by art. 246 of the Penal Code, the misappropriation of public auctions, as well as aspects of yet another incrimination, that is the one covered by art. 65 of Law no. 21/1996 republished-competition law, trying thus to prevent certain different interpretations about the typicality of the two incriminations and encourage the possibility of highlighting other arguments that will lead to an application as accurate as possible of the two incriminations. Presently there is no case law for the two incriminations therefore the theoretical analysis has to present interpretation arguments which will help the judicial bodies to easily classify the factual basis of the content of the two constitutive laws offering the possibility of a more detailed and contextual interpretation in relation to the reality. The way the public auctions take place is a constant preoccupation not only for the participants who are involved in the procedure and directly interested in abiding the under law and ensuring a fair competitive climate but also for the public opinion which is as equally interested in ensuring fair social-economical relationships based on the market principles. Simultaneously, the way the legal conditions of the second incriminations-that is the one from art.65 Law no.21/1996 republished - are interpreted in relation with the competition practices will lead to the clarification of the norm and its correct enforcement.